EVALUASI PENERAPAN PERENCANAAN PAJAK ATAS PAJAK PENGHASILAN (PPH PASAL 25) PADA PT. BANK SULUTGO - Karuniawan, Steven; Morasa, Jenny; Walandouw, Stanley Kho (JURNAL RISET AKUNTANSI GOING CONCERN, 2017)
Tax planning is one way to optimize profits because the tax is a burden / expense that reduces revenue so that efforts to reduce tax payments are often done companies. PT.Bank SulutGo in tax payments to the government has a role as one of the largest contributor to tax revenue for North Sulawesi Because PT.Bank SulutGo is a Regional Development Bank which Labanya increase every year. The purpose of this research is to know the application of tax planning to income tax Article 25 at PT. Bank SulutGo. The object of this research is Income Statement of PT. Bank SulutGo for the year ended 31 December 2016. The methodology used in this research is qualitative research. Writing method used is descriptive method that is field study by doing observation, interview, and documentation and library study. The result of evaluation of this research is expected to give information and input for company in doing tax planning as effort of tax payment efficiency to achieve maximum profit.  But still in accordance with the provisions of the applicable taxation The conclusions of this study indicate that tax planning applied by PT. Bank SulutGo is in compliance with applicable tax laws.Keywords:Tax Planning and Income Tax Article 25